Antarctic surface water intrusion triggering seasonal rapid basal melting of drygalski ice tongue, east Antarctica ... - Wang, Xianwei; Nicholls, Keith; Lee, Won Sang; Lee, Choon Ki; Stevens, Craig; Holland, David (GFZ German Research Centre for Geosciences, 2023)
<!--!introduction!--> Antarctic glaciers are losing ice rapidly to the ocean through basal melting of ice shelves/tongues. To better predicate future sea level rise, it is urgent to detect the rapid basal melting of ice shelves/tongues as well as ocean’s role in this process. In this study, basal melting of Drygalski Ice Tongue (DIT), the seaward extension of David Glacier in Northern Victoria Land, East Antarctica has been detected using a surface deployed Autonomous Phase-sensitive Radio-Echo-Sounder (ApRES). The ocean water changes adjacent to DIT front has been revealed using an ocean mooring. ApRES observation suggests a rapid basal melting > 10 m/a close to DIT front in February and mooring data shows a synchronous ocean warming in austral summer, indicating Antarctica Surface Water intrusion to the base of DIT. The mooring data has been used to simulate the basal melting of DIT front, which coincides with ApRES measurements. We conclude that rapid basal melting close to the tongue front was ... : The 28th IUGG General Assembly (IUGG2023) (Berlin 2023) ...